2009
DOI: 10.1111/j.1365-2583.2009.00887.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling of the sperm storage organs of Drosophila melanogaster

Abstract: The occurrence of female sperm storage across taxa indicates the importance of this complex and dynamic process. Organs responsible for sperm storage (SSOs) and proteins expressed therein, are important in fundamental aspects of reproduction and could play a major role in evolutionary processes such as post-mating sexual selection. Given the essential role of SSOs, it is surprising that the process of sperm storage is so poorly understood. This study investigated the transcriptome of female Drosophila melanoga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
80
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 67 publications
(116 reference statements)
0
80
0
1
Order By: Relevance
“…Significance was tested by a log-linear model. including the spermathecae and the seminal receptacle (Allen and Spradling 2008;Prokupek et al 2008Prokupek et al , 2009Prokupek et al , 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Significance was tested by a log-linear model. including the spermathecae and the seminal receptacle (Allen and Spradling 2008;Prokupek et al 2008Prokupek et al , 2009Prokupek et al , 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Ravi Ram and Wolfner (23) used such data to identify all annotated D. melanogaster genes expressed specifically in the male accessory glands and encoding putative secreted proteins. Similarly, Prokupek et al (24,25) used EST analysis and microarrays to identify genes that are up and downregulated at different time points after mating in female Drosophila sperm storage organs. A recent explosion of proteomics studies has identified many reproductive proteins in taxa ranging from crickets and honeybees to rodents and humans.…”
Section: Identifying Reproductive Proteinsmentioning
confidence: 99%
“…These mating-regulated genes may include some that are important for sperm competition. Similarly, genes expressed specifically in the female sperm storage organs (Allen and Spradling 2008;Prokupek et al 2008Prokupek et al , 2009Prokupek et al , 2010Schnakenberg et al 2011) might produce products that influence sperm competition.Many studies of the female role in sperm competition have focused on the female reproductive tract. A priori, a focus on the female reproductive tract makes sense because this is where sperm competition occurs.…”
mentioning
confidence: 99%